The Influence of Soil pH on Citrus Root Morphology and Nutrient Uptake Efficiency - Duplicate Sambani; Tripti Vashisth; Diane B. Bright; Davie M. Kadyampakeni (HortScience)
The production of citrus, a dominant fruit crop globally, is declining due to biotic constraints such as Huanglongbing (HLB) and abiotic stresses such as low or high soil pH. This study aimed to investigate the influence of soil pH on citrus root morphology, nutrient uptake dynamics, and overall root health. Forty ‘Valencia’ sweet orange [Citrus sinensis (L.) Osbeck] trees grafted on Swingle citrumelo rootstock [C. paradisis × Poncirus trifoliata (L.) Raf] were divided into four groups by pH treatment (n = 10). Trees planted in rhizotron boxes were irrigated three days a week with four different water pH levels: 5.5, 6.5, 7.5, and 8.5. Soil acidity and alkalinity were routinely monitored with pH probes. The concentration of essential macronutrients and micronutrients from the soil, plant tissue, and leachates was also analyzed monthly to evaluate nutrient uptake efficiency. Parameters such as root length, root surface area, and root diameter were measured to assess the morphological changes in citrus tree roots under different pH treatments. After irrigation, soil pH on treatment with pH = 5.5 decreased drastically since sandy soils acidify more quickly. Soil pH levels for treatments irrigated with solutions at pH 6.5 and 7.5 consistently maintained near-neutral levels, with the former gradually decreasing soil pH over time and then later increasing the soil pH to alkaline levels. The soil P and S concentrations were high at pH = 5.5, contrary to the Mg and Ca concentrations, which were low at the same pH level. Soil pH showed a significant and negative correlation with S, P, and Fe, indicating a decrease in these soil nutrients as soil pH decreased and a nonsignificant positive correlation with Cu. At pH = 5.5, there was significantly higher root growth, which indicates that acidic soils (∼pH = 5.5) can enhance root growth in citrus trees. Acidic soils stimulate root growth, particularly around a pH of 5.5; citrus roots exhibit remarkable resilience and internal compensation mechanisms in response to pH changes. Optimizing soil pH and nutrient management can mitigate the impacts of HLB and promote the resilience of citrus trees. Trees irrigated at pH of 8.5 showed a trend of fewer living roots and lower cumulative root growth, emphasizing the possibility of root damage due to high soil pH.